Factors Influencing The Incidence of Malnutrition among Toddlers in Kampung Kering Tanauli Village, Rao Subcistrict, Pasaman Regency - Rahmi Kurnia Gustin; Siti Fatimah; Syukra Alhamda (Sahabat Publikasi Kuu, 2025)
Nutrition is a problem that exists in every country, including poor, developing and developed countries. Child malnutrition is still a problem in Indonesia. It is known that until 2015 there were around 1 million children in Indonesia who were malnourished. For Pasaman District in 2016, based on the results of mass weighing conducted simultaneously, the prevalence of malnutrition was 0.9%. This figure increased in 2017 to 4.4% based on the results of Riskesdas. This study aims to determine the factors that influence the incidence of malnutrition in toddlers in Kampung Kering Tanauli Village, Rao District, Pasaman Regency. This research was conducted with descriptive analytic method with cross sectional design. The population is all mothers who have toddlers totaling 121 people and with a sample size of 55 people. Data processing and analysis were carried out by computerization using the chi square test statistical test. The results showed a relationship between education, sanitation, behavior, and socioeconomics with the incidence of malnutrition in toddlers in Kampung Kering Tanauli Village, Rao District, Pasaman Regency. It is expected that mothers can follow the development of health information, especially regarding toddlers, both through counseling activities and from print and electronic media and always actively participate in posyandu activities so that the development of the nutritional status of their toddlers can be known.